Towarzystwo Miłośników Wilna i Ziemi Wileńskiej w Gorzowie Wielkopolskim = Society of Vilnius and Wilno Land Enthusiasts in Gorzow Wielkopolski - Rother, Wilhelmina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the cultivation of Vilnius traditions and customs by Vilnius Culture Enthusiasts in Gorzow Wielkopolski.
Keywords: Vilnius; Wilno; Gorzów Wielkopolski; culture; tradition; customs; kultura; tradycja; zwyczaj